2023
DOI: 10.1093/jat/bkad002
|View full text |Cite
|
Sign up to set email alerts
|

From Bumps to Binges: Overview of Deaths Associated with Cocaine in England, Wales and Northern Ireland (2000–2019)

Abstract: Background The UK, as the ‘cocaine capital of Europe’, currently accounts for ~75% of all cocaine-related hospital admissions in Europe. This study aims to analyse trends in cocaine-related deaths in England, Wales, and Northern Ireland over 20 years (2000-2019). Methods Cases reported to the National Programme on Substance Abuse Deaths (NPSAD) occurring between 2000-2019 where cocaine was detected at post-mortem were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Cocaine ranked as the second most problematic drug for first-time treatment seekers and the second most commonly reported substance for acute toxicity by Euro-DEN Plus hospitals in 2020 (52). In the same manner, various studies conducted in different European countries have found an increase in cocaine consumption and cocaine-related deaths, also highlighting the multiple health complications related such as psychiatric and psychotic disorders, neurological maladies and cardiovascular diseases (53)(54)(55). Thus, our results seem to support Sentiment analysis (the emotional tone expressed in text).…”
Section: Discussionmentioning
confidence: 79%
“…Cocaine ranked as the second most problematic drug for first-time treatment seekers and the second most commonly reported substance for acute toxicity by Euro-DEN Plus hospitals in 2020 (52). In the same manner, various studies conducted in different European countries have found an increase in cocaine consumption and cocaine-related deaths, also highlighting the multiple health complications related such as psychiatric and psychotic disorders, neurological maladies and cardiovascular diseases (53)(54)(55). Thus, our results seem to support Sentiment analysis (the emotional tone expressed in text).…”
Section: Discussionmentioning
confidence: 79%